PERFORMA AYAM RAS PEDAGING YANG DIBERI SARI KUNYIT PUTIH (Curcuma zedoaria) SECARA ORAL - Patma Mony; Tabita Naomi Ralahalu; Sylvia Ch. H. Hehanussa (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study aimed to determine the effect of white turmeric (Curcuma zedoaria) extract given orally on the performance of broiler chickens. The research was conducted at the Livestock Unit of the Animal Husbandry Department, Faculty of Agriculture, Pattimura University, Ambon, using 96 Cobb strain broiler chickens. The study used a Completely Randomized Design (CRD) with 4 treatments and 4 replications. The treatments consisted of P0 (control), P1 (0.7 ml/bird), P2 (1.4 ml/bird), and P3 (2.1 ml/bird). The observed variables included feed consumption, body weight gain, and feed conversion. The results showed that the administration of white turmeric extract had no significant effect (P>0.05) on all observed variables. However, numerically, treatment P2 (1.4 ml/bird) showed the highest increase in body weight gain and feed efficiency. The conclusion of this study is that the oral administration of white turmeric extract is not statistically significant, but the level of 1.4 ml/bird can be considered for practical applications.